PemanfaatanBuah Nanas dan Buah Pisang KepokdalamPembuatanFruit leather - Empi Zulvarino; Evy Rossi; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The purpose of the study was to to get the best combination of pineapple (Ananas comususL. merr) and bananakepok (Musa paradisiaca) in making fruit leather.  The research used a Complete Randomized Design (CRD) with 4 treatments and 4 replications. The treatments were NP1 (Pineapple 20% :kepokbanana 80%), NP2 (Pineapple 30% : kepokbanana 70%), NP3 (Pineapple 40% : kepokbanana 60%), and NP4 (Pineapple 50% : kepokbanana 50%).  The data obtained were analyzed statistically using Anova and DMRT at 5% level.  The results showed that percentage of pineapple and banana significantly affected moisture content, ash content, degree of acidity (pH), crude fiber content, overall descriptive and hedonic sensory assessment. The best treatment of fruit leather from this research was NP1 with moisture content 11.15%, ash 0.71%, degree of acidity (pH) 4.73, and crude fiber 4.66%. The fruit leather of NP1 had brownish yellow in color (3.70), dominated by the banana with slight pineapple aroma (3.80), predominantly sweet with slightly sour taste (3.80), and the slightly chewy texture (2.20) and liked the most by the panelist.Keywords : banana kepok, fruit leather and pineapple.